PROBLEMS OF REFLECTING TERMS RELATED TO ELECTRICAL ENERGY IN TERMS - Rinatovna, Albina (Журнал иностранных языков и лингвистики, 2023)
This article is devoted to the problems of terminological work related to the normalization and standardization of terms in the field of electric power industry.The questions of variance and synonymy of terms are considered on the example of modern electrotechnical terminology.